Electron microscopy and hardness study of a semi-solid processed 27 wt%Cr cast iron - A. Wiengmoon (2018)
A semi-solid processed 27 wt%Cr cast iron was studied by electron microscopy and its microstructure was related to the hardness. In the as-cast condition, the primary proeutectic austenite was round in shape while the eutectic M7C3carbide was found as radiating clusters mixed with directional clusters. Growth in the [0 0 1]M7C3with planar faces of {0 2 0}M7C3and { 2 over(4, ̄) 0 } M7C3was usually observed with an encapsulated core of austenite. Destabilisation heat treatment followed by air cooling led to a precipitation of secondary M23C6carbide and a transformation of the primary austenite to martensite in the semi-solid processed iron. Precipitation behaviour is comparable to that observed in the destabilisation of conventional cast iron. However, the nucleation of secondary M23C6carbide on the eutectic M7C3carbide was observed for the first time. Tempering after destabilisation led to further precipitation of carbide within the tempered martensite in the eutectic structure. The maximum hardness was obtained after destabilisation and tempering heat treatment due to the precipitation of secondary carbides within the martensite matrix and a possible reduction in the retained austenite. © 2007 Elsevier B.V. All rights reserved.